Insect Growth Regulatory Activity of Blechnum chilense (2011)
The genus Blechnum has 13 species that are common plants, well-distributed in Chile. Here, we report a phytochemical analysis of B. Chilense (Kaulf.) Mett., as well as the insecticidal effects of extracts of this plant. From the n-hexane fraction four phytoecdysones were isolated: ecdysone, ponasterone, shidasterone and 2-deoxycrustecdysone. A bioassay with Drosophila melanogaster larvae was used to evaluate insecticidal activity. The EtOAc and n-hexane fractions at 800 ppm caused 66.7 and 50.0% larval mortality, respectively. Treatments with both extracts at 800 ppm caused the greatest larval mortality, whereas treatments with 500 and 200 ppm induced premature pupation compared with the control and the highest adult mortality, probably due to interference with ecdysteroid metabolism and inhibition of ecdysis triggering hormone (ETH). The dead adult flies exhibited malformations.